MODERN LEARNING PROCESS IN QUESTIONS AND ANSWERS - Миер, Татьяна (SWorldJournal, 2020)
In the work the form of "question - answer" presents current aspects of the modern learning process. It is about variable in the educational process and relatively sustainable, which creates a basis for the introduction of innovation. It is considered fou